Kito-ryu jujutsu and the desolation of Kodokan judo’s Koshiki-no-kata -Remembering Inoue Shoji (1927-2018) (Revista de Artes Marciales Asiáticas, 2018)
Inoue Shoji (1927-2018) was born in Tokushimaprefecture, Japan. As a youngster he took up judo. Later, he studied Kito-ryu jujutsu for some time with Odaka Shigeru. During his professional career as a prison guard he followed up on an offer to become a judo therapist. In a dojo in the Yamashina-ku ward in Kyoto he taught both judo and a limited catalogue of Kito-ryu that included exercises that were adopted into Kodokan judo under the name koshiki-no-kata [The Antique Forms]. With Kodokan judo continuing to deteriorate into an ordinary sport and losing its core values and purpose, Inoue increasingly appreciated the traditional martial arts values preserved in Kito-ryu jujutsu. His enthusiasm was reflected in beginning to give public demonstrations at various events in Japan and becoming a representative of Kito-ryu in the Nihon Kobudo Kyokai. Inoue’s supreme moment of glory likely was his public demonstration in 2013 at the occasion of the Fifth International Judo Federation (IJF) World Kata Judo Championships held in Kyoto. It was this performance that introduced him to the international judo community and brought him certain fame. For most foreign judoka this was their first contact with Kito-ryu. Irrespective of the quality of Inoue’s display, his approach offered a counterweight against the Kodokan’s historic reinvention and the IJF sports kata caricature. Several video clips publicly available on YouTube remain as a lasting memory of his art. Inoue Shoji held the rank of Kodokan 8th dan, and peacefully died in Kyoto on October 30th, 2018.